IMMUNOCYTOCHEMICAL LOCALIZATION OF UBIQUITIN IN DEVELOPING OCCIPITAL AND PREFRONTAL CORTEX OF HUMAN FETAL BRAIN DURING SECOND TRIMESTER - T. S. KHEDKAR,; Y. A. GADHIKAR,; S. A. KOUSHIK, (The Bioscan, 2012)
Ubiquitin immunoreactive profiles were studied in developing human fetal occipital cortex and the prefrontal cortex during the second trimester. We employed immunolabelling techniques on seven human fetal occipital cortices and prefrontal cortices ranging from 12 weeks gestation (w.g.) to 25w.g. by using ubiquitin antibody. At the end of first trimester, immunoreactive profiles were relatively meager in both the areas. In 12w.g. moderate to intense ubiquitin immunoreactivity was detected in the marginal zone (MZ) and ventricular zone (VZ), where as fibrous layer at this stage showed diffuse nonspecific immunoreactivity. At 17 weeks occipital and prefrontal cortex, staining was restricted to the cells while at 18, 19, 20w.g. immunoreactive product was observed in the fibrous network. At 22w.g. ubiquitin immunoreactivity was detected in the fibrous network of occipital cortex while wide spaces were detected in the fibrous layer of prefrontal cortex. With the increase in fetal age i.e. 25w.g, the ubiquitin reactivity was almost absent in both the areas viz. prefrontal cortex and occipital cortex. We suggest that expression of ubiquitin in the occipital and prefrontal cortex may be of transient occurrence during the second trimester.